Sandwiched structure for temperature compensated laterally excited bulk wave resonators based on lithium niobate film - Yahui Tian; Rufan Du; Qiaozhen Zhang; Feida Cai; Honglang Li; Qipeng Lu (AIP Advances, 2024)
Recently, lithium niobate thin film laterally excited bulk wave resonators (XBARs) have attracted much attention because of their advantage of high frequency and outstanding electromechanical coupling factor (K2) enabling wide filter bandwidths. These can satisfy the increasing 5G communication demand. However, their large temperature coefficient limits their development to some extent. To improve their temperature stability with little K2 reduction, this paper has proposed a sandwiched structure for temperature compensated XBARs (TC XBARs). This structure includes the top silicon dioxide (SiO2) layer and the bottom SiO2 layer. One layer can improve temperature stability, and the other layer can increase K2. The optimized XBARs have a temperature coefficient of frequency (TCF) of −90.77 ppm⁄°C. The common two-layer TC XBARs can achieve a TCF of −22 ppm⁄°C sacrificing K2 to 8%. However, the proposed sandwiched TC XBARs can achieve a K2 of 12.15 and a TCF of −28.94 ppm⁄°C simultaneously, with a large FoM. Meanwhile, spurious modes can be suppressed in the sandwiched structure. Thus, this sandwiched structure can provide a good solution for the high performance of XBARs.